2017
DOI: 10.1002/2017jf004356
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Coherent Flow Structures Over Subaqueous High‐ and Low‐ Angle Dunes

Abstract: Large‐scale coherent flow structures (CFSs) above dunes are the dominant source of flow resistance and constitute the principal mechanism for sediment transport and mixing in sand bed river and estuarine systems. Based on laboratory observations, CFS formation has been previously linked to flow separation downstream of high‐angle dunes with lee slopes of ~30°. How CFSs form in natural, deep rivers and estuaries where dunes exhibit lower lee slopes and intermittent flow separation is not well understood. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…The quantification of reattachment length (Figure ) indicates that a measure of flow magnitude and the shape of velocity profiles provide a more universal description of reattachment length for a given dune geometry. Parameterization of this relationship into models such as those of Paarlberg et al () and Lefebvre et al () will require additional work measuring velocity profiles and median reattachment lengths across a range of dune geometries, including low‐angle dunes, as well as considering the inclusion of brink‐point shape into dune morphology (Kwoll et al, , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The quantification of reattachment length (Figure ) indicates that a measure of flow magnitude and the shape of velocity profiles provide a more universal description of reattachment length for a given dune geometry. Parameterization of this relationship into models such as those of Paarlberg et al () and Lefebvre et al () will require additional work measuring velocity profiles and median reattachment lengths across a range of dune geometries, including low‐angle dunes, as well as considering the inclusion of brink‐point shape into dune morphology (Kwoll et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments on the ripple-dune transition (Bennett & Best, 1996;Fernandez et al, 2006;Frias & Abad, 2013;Schindler & Robert, 2005) showed that during the transition, the location and intensity of flow separation (Figure 1, point 2), the turbulent wake (Figure 1), and the height of the internal boundary layer (Figure 1, point 4) vary in their spatial location and intensity. Best and Kostaschuk (2002) and Kwoll et al (2016Kwoll et al ( , 2017 have also shown that reductions in the leeside slope angle lessen the intensity and temporal consistency of flow separation (Figure 1, point 2), while Bennett et al (1998) and Naqshband et al (2016) examined the transition of dunes to upper stage plane bed and demonstrated the collapse of the flow separation feedback. All these experiments indicate deviations from the equilibrium dune flow description ( Figure 1) due to alteration of the bed morphology.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The fluid is seeded with tracer particles that are assumed to follow the flow dynamics. PIV has proven suitable for measurements of flow velocity [17][18][19] and provided detailed information on flow structures, such as large-scale coherent flow structures above dunes [18]. Tools for the application of PIV are readily available.…”
Section: Piv-based Particle Motion Tracking With the Use Of Images Ofmentioning
confidence: 99%
“…Estimation from local velocity profiles over the trough overpredicts total shear stress, while that from the crest fits well with the result of spatial averaging (Figure 4-1). It indicates that although the accuracy of technique of spatial averaging are relevant to bedform characteristics (lee-side angle), flow separation and flow strength Kwoll et al, 2017], for low-angle dunes, shear stress over the crest can roughly represent total stress of spatially averaged.…”
Section: What Are the Characteristics Of τ τ τ τ Over Low-angle Dunes?mentioning
confidence: 99%